THE EFFECT OF ELECTROLYTES ON POLYMER VISCOSITY FOR EFFECTIVENESS OF POLYMER INJECTION - Yani Faozani Alli (Scientific Contributions Oil and Gas, 2019)
The use of polymer for tertiary oil recovery has been known to be important as viscosity modifier to increase sweep efficiency of water flood and chemical flood. The most common polymer used for chemical flood is hydrolyzed polyacrylamide (HPAM) that owing large number of charges along the polymer chains. However, formation water as dissolution water contain high electrolytes that has a great effect on polymer viscosity, as well as responsible to generate the efficiency of polymer flooding. In this study, the effect of electrolytes from saline and cation divalent to the viscosity of polymer was investigated. Three studied polymers were dissolved in various concentration of saline and cation divalent by analyzing the compatibility, viscosity, and the filtration ratio of polymers. The results showed that the presence of electrolytes in every concentration of water did not impact the compatibility and filtration ratio of polymers. Whereas, the addition of sodium chloride as saline ionic and calcium chloride as cationic divalent were both reducing the viscosity of polymers. The lower viscosity of polymer related to the ability of polymer to expand the hydrodynamic which limited by the neutralization of internal repulsion of the electrolytes.